Compliance, enterprises and corruption: An international glance - Sanclemente-Arciniegas, Javier (2020)
This paper raises a reflection on the legal notion of compliance and the way in which it involves companies in the fight against corruption. That is a new global regulatory trend that provides useful tools to address different legal fields, hence some authors consider it a new branch of law. The notion is articulated around a new conception of companies that tends to effectively engage them with the protection of legally relevant values. These postulates are especially relevant in the fight against corruption. In this area, the tendency to establish private economic power as an agent in the service of the protection of the general interest is clearly manifested. For this, on one hand, the common legislative movement at the international level is analyzed, identifying norms that have been adopted by different states in the world in order to involve companies in the fight against corruption. On the other hand, we analyze the normative and institutional devices that companies have adopted in order to meeting those obligations. There we highlight the way in which companies are transformed from entities dedicated to obtaining particular benefits to actors that serve interests of the whole society, when addressing the risk of regulatory non-compliance.